2011
DOI: 10.1017/s1355617711000646
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Learning Strategy Following Mild Traumatic Brain Injury

Abstract: That learning and memory deficits persist many years following mild traumatic brain injury (mTBI) is controversial due to inconsistent objective evidence supporting subjective complaints. Our prior work demonstrated significant reductions in performance on the initial trial of a verbal learning task and overall slower rate of learning in well-motivated mTBI participants relative to demographically matched controls. In our previous work, we speculated that differences in strategy use could explain the differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Additionally, it is possible that the use of more specialized neuropsychological tests [or subsections of such tests, see Ref. (12, 13)] may have identified and isolated more discrete cognitive deficits. Such detailed assessments may have provided measures of cognitive impairment that might have been more associated with the biological measures of WM integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is possible that the use of more specialized neuropsychological tests [or subsections of such tests, see Ref. (12, 13)] may have identified and isolated more discrete cognitive deficits. Such detailed assessments may have provided measures of cognitive impairment that might have been more associated with the biological measures of WM integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors stipulate that the magnitude of mTBI-related effects within each cognitive domain remains unclear as the respective effect sizes for “cognitive deficits” appear especially heterogeneous across meta-analyses (i.e., d  = −0.11 to 0.72) and that these higher order functions appear most susceptible to multiple mTBI [ d  = 0.24 (11)]. Recent reports also suggest that mTBI patients may, in fact, experience subtle cognitive deficits that reflect diminished initial acquisition of novel information (12, 13). Specifically, mTBI patients demonstrated statistically significant deficits in performance on the first trial of the California Verbal Learning Task, whereas there were no impairments on total learning or memory composite variables (12).…”
Section: Introductionmentioning
confidence: 99%
“…A perfect example is a recent study from Geary and colleagues, who show that traditional mean and standard deviation measures of verbal memory, based on California Verbal Learning Test (CVLT) performance, were non-significant and therefore conventional analyses were insufficient in detecting any mTBI effects (Geary et al, 2011). In contrast their study revealed significant differences when methods that tapped different strategies of verbal learning were used; concluding that, ''Despite achieving comparable total learning scores .…”
Section: Sensitivity Of Neuropsychological Measures To Persistent Effmentioning
confidence: 99%
“…We believe there is little argument with the above statement-the majority of mTBI patients over time enjoy a full functional return to their pre-injury baseline and their recovery follows a quick and rather benign course. However, some mTBI patients do experience persisting neurocognitive and neurobehavioral deficits and symptoms (Risdall & Menon, 2011), even after controlling for such factors as depression and potential response bias (Geary, Kraus, Rubin, Pliskin, & Little, 2011;Konrad et al, 2010). If return to baseline level of function is the norm in mTBI, and this recovery occurs within hours to days or within a few weeks, repeat neuropsychological studies that track mTBI outcome will evidence fewer findings over time that indicate any cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, deficits in learning strategies, such as impaired semantic organization, have been demonstrated (Carlesimo, Sabbadini, Loasses, & Caltagirone, 1997;Crosson et al, 1988;Geary, Kraus, Rubin, Pliskin, & Little, 2011;Goldstein, Levin, & Boake, 1989;Levin & Goldstein, 1986) and generally interpreted as indicating impaired encoding. However, an alternative explanation is that these organizational difficulties reflect executive dysfunction, rather than a memory encoding deficit.…”
mentioning
confidence: 99%